Assessing the Reliability and Validity of the Chester Step Test 2 to Predict Aerobic Capacity. - Burt, Dean; Forsyth, Jacky; Jones, Sam; Buckley, John (Measurement in Physical Education & Exercise Science)
The Chester Step Test (CST) is used in occupational and healthcare settings to estimate cardiovascular fitness ($\dot V{O_{2\max }}$ V ˙ O 2 max ); however, in attempts to overcome $\dot V{O_{2\max }}$ V ˙ O 2 max - prediction error, a revised version has been developed (CST2). This study investigated the test–retest reliability and criterion validity of the CST2. In a randomized order, at the same time of day, with at least 24 hours rest between trials, 50 healthy participants (32 males, 18 females, age: 34.9 ± 10.9 y, body mass: 79.1 ± 14.5 kg, stature: 174.3 ± 10.9 cm) completed the CST2 twice (CST2a; CST2b) and a treadmill-based $\dot V{O_{2\max }}$ V ˙ O 2 max test. Test–retest reliability and criterion validity were examined using a repeated measures ANOVA and the 95% limits of agreement (LoA). No significant bias was reported between the CST2a and CST2b predicted and actual $\dot V{O_{2\max }}$ V ˙ O 2 max (p >.05). The bias ±95% LoA (−0.48 ± 3.4 ml.kg−1.min−1) suggest that the CST2 is a reliable predictor of $\dot V{O_{2\max }}$ V ˙ O 2 max . However, the bias ±95% LoA between the CST2 predicted and actual $\dot V{O_{2\max }}$ V ˙ O 2 max ranged from 1.08–1.6 ± 11–11.5 ml.kg−1.min−1, translating to a 31% prediction error. The CST2 is a reliable measure of $\dot V{O_{2\max }}$ V ˙ O 2 max however should only be considered when an estimate is required.